The Impact of Sparking Leadership on Creating Work Passionand Job Satisfaction in Organizations – An Empirical Study - (:unkn) unknown (My University, 2021)
In the highly competitive work environment of today, employees seem to be lacking work passion. Work passionis the inner fire. Leaders who ignite spirit, encourage passion and light the spark in employees to create the fire intheir work environment are called the “sparking leaders”. The sparking leaders play an important role inorganizations, but theoretical understanding of who they are and what impact they have in organizationaloutcomes is lacking. The present paper builds on fragmented and disparate extant work to conceptualize thenature of sparking leadership associated with work passion and job satisfaction of the employees. Consistent withthe theoretical foundation behind previous research, the findings of the study reveal that sparking leaders have apositive effect on the subordinates’ work passion, which further leads to a higher job satisfaction. This means thatthe sparking leaders create the fire in an organization so that their work passion energizes their subordinates.

Günümüzün oldukça rekabetçi iş ortamında, çalışanlar iş tutkusundan yoksun gibi görünmektedirler. İş tutkusu içsel ateştir. Ruhu ateşleyen, tutkuyu teşvik eden ve çalışma ortamlarındaki yangını yaratmak için çalışanlarını kıvılcımlandıran liderler “ateşleyici liderler” olarak adlandırılmaktadır. Ateşleyici liderler örgütlerde önemli bir rol oynamaktadır. Ancak bu liderlerin kimler oldukları ve örgütsel çıktılarda nasıl bir etkiye sahip olduklarına dair teorik kavrayış yetersizdir. Ateşleyici liderliğin doğasını kavramsallaştırmak için parçalanmış ve farklı çalışmalar üzerine inşa edilmiş olan bu çalışmada, ateşleyici liderlik, çalışanların iş tutkuları ve iş tatminleri ile ilişkilendirmiştir. Daha önce yapılmış olan araştırmaların arkasındaki teorik temel ile uyumlu olarak, bu çalışmanın bulguları, ateşleyici liderlerin astlarının iş tutkuları üzerinde olumlu bir etkiye sahip olduklarını ve bunun daha yüksek bir iş tatminine yol açtığını göstermektedir. Bu, ateşleyici liderlerin iş tutkularıyla astlarına enerji verebilmek amacıyla bir örgütü ateşe verdiklerini göstermektedir.
Ateşleyici Liderliğin Örgütlerde İş Tutkusu ve İş Tatmini Üzerindeki Etkisi – Ampirik Bir Çalışma